Turning the optical properties of microcrystalline diamond films by boron ion implantation and annealing - Dan Dai; Jiale Wang; Chengke Chen; Haitao Ye; Nianhua Peng; Jinping Pan; Xiaojun Hu (Functional Diamond, 2024)
We investigated the correlation between microstructures and optical properties of boron ion implanted microcrystalline diamond (B-MCD) thin films annealed at different temperatures. Ellipsometry characterization of B-MCD films was performed in the wavelength range of 380–1000 nm and the disperse parameters of the films such as single oscillator energy and dispersive energy were uniquely determined by using a Gaussian model. The results show that the refractive index increases from 2.18 to 2.21 to 2.28–2.29 with annealing temperature increasing from 700 to 800 °C and then it slightly decreases to 2.25–2.28 with annealing temperature further increasing to 900 °C, implying that the annealing temperature has a significant impact on the optical properties of B-MCD films. Raman spectra reveal that the full width at half maximum of diamond peak significantly decreases after 800 °C annealing, indicating a better quality of diamond crystalline. X-ray photoelectron spectroscopy results show that this sample contains higher sp3 carbon content, lower sp2 and C–O contents on the film surface after 800 °C annealing, implying that fewer defects exist. The results are of great significance for the preparation of excellent boron ion implanted microcrystalline diamond for waveguide based Mach-Zehnder Interferometer liquid sensing.